Rhythmic Gymnastics Activities on Gross Motor Development in Early Childhood - Atirah Ahdal; Herlina Herlina; Herman Herman; Wahira Wahira; Surya (International Journal of Multidisciplinary Approach Research and Science, 2026)
Early childhood gross motor development is crucial to support physical activity, coordination, and independence, as stipulated in Law No. 20 of 2003 concerning the National Education System, which emphasizes physical stimulation from an early age. Early observations showed a lack of structured activities, such as rhythmic gymnastics, in early childhood education, leading to gross motor delays in skills like jumping and running, even though conventional activities were available. Rhythmic gymnastics, with musical accompaniment and rhythmic movements, is considered effective in stimulating large muscles based on the theories of Gallahue and Ozmun. The study aims to test the effectiveness of rhythmic gymnastics with the theme "Great Indonesian Children" compared with conventional gymnastics in improving the gross motor development of children aged 5-6 years. Focus on significant pretest-posttest differences between experimental and control groups to prove the effect of the intervention. This study uses a quasi-experimental design, specifically a Nonequivalent Control Group Design. The experimental group received the rhythmic gymnastics of Anak Indonesia Hebat (2-3 times/week, 30-45 minutes), while the control group received conventional gymnastics. Data were collected through pretest-posttest observations using sheets based on indicators of balance, coordination, agility, and strength. The analysis included descriptive statistics (mean, N-Gain), the Shapiro-Wilk normality test, Levene's test of homogeneity, and the Wilcoxon Signed-Rank and Rank-Sum Tests R RStudio. The experimental group showed an average increase from 38.12 (pretest) to 77.08 (posttest), a moderate-to-high N-Gain (75% moderate, 25% high), and a significant difference (p=0.002459). The control group increased from 38.75 to 41.46, but the N-Gain was low and insignificant (p=0.07006). The difference between the posttest groups was significant (p=3.134e-05, Wilcoxon Rank-Sum). The rhythmic gymnastics activity Anak Indonesia Hebat significantly improves the gross motor skills of children aged 5-6 years, outperforming conventional methods. Implications: Integrate thematic gymnastics into the PAUD curriculum to optimize physical development, support advanced research on external factors, and provide teacher training in Indonesia.